2014
DOI: 10.1007/s00428-014-1615-5
|View full text |Cite
|
Sign up to set email alerts
|

Expression of PD-1 (CD279) and FoxP3 in diffuse large B-cell lymphoma

Abstract: The role of the microenvironment in high-grade lymphoma is not well defined. In this report, we employ immunohistochemistry to characterise programmed death-1 (PD-1/CD279) and FoxP3 expression in 70 cases of diffuse large B-cell lymphoma (DLBCL). PD-1 is a surface marker characteristic of follicular helper T-cells whilst FoxP3 is characteristic of Tregs. We demonstrate variable infiltration with CD4(+) T-cells (<10 to >50 % of all lymph node cells) and PD-1(hi) cells (0.1 to 1.5 % of all cells). CD4(+) T-cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 40 publications
3
60
0
Order By: Relevance
“…75 It is also likely that biological behavior and prognosis are determined not only by overall PD-1 + TILs and tumor cells, but by functionally distinct subsets. PD-1 + numbers correlated with CD4 + T-cell and FoxP3 + numbers and GrB and TIA-1 + cells in several studies, 42,52,72 and similar associations were found between distribution patterns of FoxP3 + and PD-1 + cells. Modulating effects might also be exerted by other microenvironment components such as TAMs, 35 tumor-associated histiocytes, 37 and small vessels.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…75 It is also likely that biological behavior and prognosis are determined not only by overall PD-1 + TILs and tumor cells, but by functionally distinct subsets. PD-1 + numbers correlated with CD4 + T-cell and FoxP3 + numbers and GrB and TIA-1 + cells in several studies, 42,52,72 and similar associations were found between distribution patterns of FoxP3 + and PD-1 + cells. Modulating effects might also be exerted by other microenvironment components such as TAMs, 35 tumor-associated histiocytes, 37 and small vessels.…”
Section: Discussionsupporting
confidence: 76%
“…While actual median values were not reported, the numbers of PD1 + T FH (P=0.0007), FoxP3 + (P=0.0069), and total CD4 + cells (P=0.04) above the median were associated with improved overall survival (OS), and had independent prognostic significance in multivariate analyses. 42 This was confirmed in more recent studies; although the quantity of PD-1 + TILs showed no significant association with clinicopathological variables, the presence of PD-1 + TILs (score 1-3) significantly prolonged OS (P=0.026) and progression-free survival (PFS) (P=0.005), and was an independent favorable prognostic factor in multivariate analyses. 38 In contrast, in another study, patients with PD-1 expression >20/hpf had a trend to poorer OS (P=0.120).…”
Section: Prognostic Relevance Of Pd-1 Expression In Dlbclsupporting
confidence: 57%
See 1 more Smart Citation
“…PD-1 and its ligand, programmed cell death ligand 1 (PD-L1), interact to downregulate the activation of T cells in autoimmune disease, chronic infection, and cancer [4,5]. PD-1 is also known to activate the transcription factor Foxp3, and is correlated with Foxp3 expression [6]. Several recent reports have demonstrated a correlation between PD-1 expression and prognosis in cancer patients.…”
Section: Introductionmentioning
confidence: 98%
“…[14,15] In diffuse large B-cell lymphoma (DLBCL), PD-1 was expressed on tumor-infiltrating lymphocytes (TILs), and the number of PD-1 + TILs was associated with the favorable overall survival (OS) in patients with DLBCL. [16,17] Besides, the higher expression of PD-L1 was also found in tumor cells and it maybe a potential biomarker for DLBCL. [18] Thus, the PD-1/PD-L1 pathway may also contribute to the proliferation of tumor cells of DLBCL and may be a novel applicable strategy to treat patients with DLBCL.…”
Section: Introductionmentioning
confidence: 99%